A A Quantitative Examination of Housing Price Determinants in Yogyakarta - Bagas Yudhanto Aji; Elit Rizki Wijaya; Juliana Diva Putri Raharjo; Nurul Fazillah; Nuke Allya Nurmadina (Universitas Muhammadiyah Surakarta, 2025)
This study examines the determinants of housing prices in Yogyakarta, focusing on structural property features such as land area, bedrooms, bathrooms, vehicle slots, and house area. Utilizing a quantitative approach with multiple linear regression on secondary data, the research identifies land area as the most significant predictor of property value, followed by bedrooms and bathrooms. Vehicle slots provide moderate influence, while house area shows a lesser impact. These findings highlight the critical role of land scarcity and urban growth in shaping housing prices, offering actionable insights for policymakers, urban planners, and developers. Future studies should explore qualitative factors like neighborhood quality and cultural influences to complement these results.